Concurrent Use of Oral Anticoagulants and Sulfonylureas in Individuals With Type 2 Diabetes and Risk of Hypoglycemia: A UK Population-Based Cohort Study - Alwafi, Hassan; Wong, Ian C. K.; Naser, Abdallah Y.; Banerjee, Amitava; Mongkhon, Pajaree; Whittlesea, Cate; Alsharif, Alaa; Wei, Li (Frontiers in Medicine, 2022)
OBJECTIVE: To investigate the association of concurrent use of oral anticoagulants (OACs) and sulfonylureas and the risk of hypoglycaemia in individuals with type 2 diabetes mellitus (T2DM). RESEARCH DESIGN AND METHODS: A retrospective cohort study was conducted between (2001-2017) using The Health Improvement Network (THIN) database. Individuals with T2DM who received OAC prescription and sulfonylureas were included. We compared the risk of hypoglycaemia with sulfonylureas and OACs using propensity score matching and Cox regression. RESULTS: 109,040 individuals using warfarin and sulfonylureas and 77,296 using direct oral anticoagulants (DOACs) and sulfonylureas were identified and included. There were 285 hypoglycaemia events in the warfarin with sulfonylureas group (incidence rate = 17.8 per 1000 person-years), while in the sulfonylureas only, 304 hypoglycaemia events were observed (incidence rate = 14.4 per 1000 person-years). There were 14 hypoglycaemic events in the DOACs with sulfonylureas group (incidence rates = 14.8 per 1000 person-years), while in the sulfonylureas alone group, 60 hypoglycaemia events were observed (incidence rate =23.7 per 1000 person-years). Concurrent use of warfarin and sulfonylureas was associated with increased risk of hypoglycaemia compared with sulfonylureas alone, (HR 1.38; 95% CI 1.10–1.75). However, we found no evidence of an association between concurrent use of DOACs and sulfonylureas and risk of hypoglycaemia (HR 0.54; 95% CI, 0.27–1.10) when compared with sulfonylureas only. CONCLUSIONS: We provide real-world evidence of possible drug-drug interactions between warfarin and sulfonylureas. The decision to prescribe warfarin with coexistent sulfonylureas to individuals with T2DM should be carefully evaluated in the context of other risk factors of hypoglycaemia, and availability of alternative medications.